50-FOLD Enrichment of CD34+ cells directly from cord blood in a single density separation - Peters, C.E; Clarke, E; Glimm, H; Lansdorp, P.M; C.J.Eaves; Thomas, T.E (Experimental hematology, 2000)
To date, extensive enrichment of progenitor cells from cord blood has required at least two steps, with cell losses incurred at each step. We have developed a simple technique, called RosetteSep™, to enrich progenitor cells directly from whole cord blood in a single step, significantly reducing the cell losses seen with other multi-step systems. This approach combines the specificity of antibody (Ab) mediated cell separation with the ease of density gradient centrifugation. A cocktail of bispecific Ab reagents selectively couples cell surface antigens on unwanted cells to erythrocytes present in the sample, producing cell/RBC rosettes. The rosetted cells are pelleted in a standard Ficoll (1.077 g/mL) separation; the desired, unlabeled cells are recovered at the Ficoll:plasma interface. Progenitors were enriched from whole cord blood using two different Ab cocktails: a 4 Ab cocktail (anti- CD2, CD14, CD19, and CD66b) and an 8 Ab cocktail (anti- CD2, CD3, CD14, CD16, CD19, CD24, CD56, and CD66b). Enrichment and % recovery of colony forming cells (CFC) with the 4 Ab cocktail was 9 ± 2 fold and 43 ± 4%, and with the 8 Ab cocktail was 40 ± 9 fold and 43 ± 15%. In summary, the RosetteSep™ method offers high purity and high recovery of progenitors directly from whole cord blood.